Advances and challenges in the medical approach to cases of violence against women: Reflections on identification, treatment and comprehensive support - Pinto, Camila Karielle Sousa Carvalho; Mota, Eduarda Queiroz; Cruz, Gabriel Lopes da; Vieira, Gabryella Trindade; Nogueira, Gustavo Silva; Oliveira , Hanne Karoline Lopes; Gomes, Heloisa Cardoso; Negreiros, Maria Eduarda Mourão; Silva, Vitor Emanoel Barbosa da; Faria, Yasmin Gondim de Paiva (Seven Editora, 2024)
The medical approach in cases of violence against women is essential for early identification, appropriate treatment, and support for victims. Healthcare professionals play a crucial role in assessing and treating physical injuries, as well as in considering and addressing the emotional repercussions of abuse. In addition, guidance to support resources, such as psychological and legal services, is critical. The training of health professionals to deal sensitively with these situations contributes to an integrated approach, recovering the physical and emotional recovery of women in situations of violence. DOI:https://doi.org/10.56238/sevened2024.001-011